A Designed Twist Sensor Based on the SPR Effect in the Thin-Gold-Film-Coated Helical Microstructured Optical Fibers - Mengwei Zhang; Lei Zhang; Qiang Chen; Ge Bai; Shuguang Li (Sensors, 2022)
The traditional optical fiber-based twist sensing has the disadvantage of low sensitivity and difficulty of distinguishing the twist direction. Moreover, chiral isomerism may lead to sensing errors. In this paper, a six-hole helical microstructured optical fiber (HMSF) with a thin-gold-film-coat based on the surface plasmon resonance (SPR) effect was designed. The twist sensing characteristics of this fiber were further analyzed. Numerical calculation and analysis show that the combination of helical effect and SPR effect can design an HMSF-based sensor that is very sensitive to distortion. In the torsion range of ±300°, the distortion sensitivity can reach 2470.7 pm/(rad/m), and the linear correlation coefficient is 0.99996. Based on the special sensing mechanism, it has a good linear coefficient over a large range. Additionally, the direction of the twist can be easily discerned. The HMSF in this work not only has high sensitivity, high linearity, high fault tolerance rate, and a wide range of measurement, but is also easy to manufacture. Therefore, it is promising in the field of twist sensing and has a good application prospect.